Impact of a hospital‐wide sepsis pathway on improved quality of care and clinical outcomes in surgical patients at a comprehensive cancer centre. (13th February 2019) - Hiong, Alison; Thursky, Karin A.; Venn, Georgina; Teh, Benjamin W.; Haeusler, Gabrielle M.; Crane, Megan; Slavin, Monica A.; Worth, Leon J.
Abstract: Purpose: Sepsis is a significant complication following cancer surgery. Although standardised care bundles improve sepsis outcomes in other populations, the benefits in cancer patients are unclear. The objectives of this study were to describe the epidemiology of sepsis in cancer patients post‐surgery, and to evaluate the impact of a clinical sepsis pathway on management and clinical outcomes. Methods: A standardised hospital‐wide sepsis pathway was developed in 2013, and all cases of sepsis at the Peter MacCallum Cancer Centre in 2014 were retrospectively evaluated. Inclusion criteria were sepsis onset during the 100‐day period following a surgical procedure for cancer diagnosis. Patients were identified using ICD‐10‐AM sepsis discharge codes, audit documentation and the hospital's antimicrobial approval system. Sepsis episodes were classified as managed on‐ or off‐pathway. Results: A total of 119 sepsis episodes were identified. Of these, 71 (59.7%) were managed on the sepsis pathway. Episodes managed on‐pathway resulted more frequently in administration of appropriate antibiotics compared to those off‐pathway (94.4% vs. 66.7%, p  < 0.001), and had shorter time to first‐dose antibiotics (median 85 vs. 315 min, p  < 0.001). Pathway utilisation was associated with significant reductions in need for inotropes (7% vs. 13%, p  = 0.023), ventilation (3% vs. 10%, p  = 0.006) and length of hospitalisation (median 15 vs. 30 days, p  = 0.008). The most frequent source of infection was organ‐space surgical site infection (24.4% of instances). Conclusions: A dedicated hospital‐wide sepsis pathway had significant impact on the quality of care and clinical outcomes of sepsis in cancer surgery patients. Cost‐benefit analysis of sepsis pathways for cancer patients is required.